Characterization of the Neurospora crassa GH72 family of Laminarin/Lichenin transferases and their roles in cell wall biogenesis - Apurva Chatrath; Pavan Patel; Protyusha Dey; Stephen J. Free (The Cell Surface)
In Neurospora crassa vegetative hyphae, chitin, β-1,3-glucan (laminarin), and a mixed β-1,3−/β-1,4-glucan (lichenin) are the major cell wall polysaccharides. GH72 enzymes have been shown to function as β-1,3-glucanases and glucanosyltransferases and can function in crosslinking β-1,3-glucans together. To characterize the enzymatic activities of the N. crassa enzymes, we expressed GEL-1 with a HIS6 tag in N. crassa. A chimeric maltose binding protein:GEL-2 was produced in E. coli. Purified GEL-1 and GEL-2 were used to characterize their enzymatic activities. We employed thin-layer chromatography (TLC) and polyacrylamide carbohydrate gel electrophoresis (PACE) assays to visualize GEL-1 and GEL-2 hydrolase and transferase activities on lichenin and laminarin substrates. We determined that GEL-1 functions as a laminarinase (β-1,3-glucanase) and as a laminarin transferase. We found that GEL-2 can function as a laminarinase and as a licheninase (β-1,3−/β-1,4-mixed-glucanase) and can crosslink β-1,3-glucans together. We demonstrated that GEL-2 can form enzyme:lichenin intermediates, providing evidence that GEL-2 functions as a lichenin transferase as well as a β-1,3-glucan transferase and crosslinks both types of polysaccharides into the N. crassa cell wall.